INTELLECTUAL CAPITAL, FINANCIAL CRISIS AND PERFORMANCE OF ISLAMIC BANKS: DOES SHARIAH GOVERNANCE MATTER? - Nawaz, Tasawar (International Journal of Business and Society, 2017)
This paper empirically examines the impact of intellectual capital (IC) and Shariah governance on economic performance of 47 Islamic banks (IBs) operating in the Gulf Cooperation Council (GCC) region in pre- and post-financial crisis period. The analysis suggests that higher IC efficiency helps IBs to improve their odds of survival at all times i.e. before- and after-crisis. Further, higher IC efficiency helps IBs to maintain their profitability i.e. ROA and market valuation i.e. Tobin’s Q at all times. Arguably, knowledge-resources i.e. IC is the main line of defence for IBs against negative shocks. Lastly, the study reveals that Shariah governance alone may fall short in explaining the growth trends in Islamic finance industry. Keywords: Intellectual Capital; Shariah Governance; Financial Crisis; Islamic Worldview; Economic Performance.